Pengaruh Pemberian Tepung Rumput Laut pada Ransum Ayam Broiler terhadap Kadar Lemak dan Kolesterol - Juniarti, Nurinsan; Ngitung, Rosdiana; Hiola, St. Fatmah (bionature, 2019)
Abstract. This research aimed to know the effect of seaweed meal at broiler chicken rations to fat level and cholesterol. This research using an experimental with Completely Randomized Design (CRD) with 4 treathments and 6 replications. Each treatment had 5 chickens test, so a total of 120 chickens test. The treatments given of the ration treatment without seaweed meal as control, ration with seaweed meal 3%, ration with seaweed meal 5%, ration with seaweed meal 7%. The parameters growth of broilers was the body weight chickens test did every week, carcass percentage, thorax percentage and abdominal fat percentage did at the end of experiment were after broiler 42 days. The data obtained were analyzed using analysis of variance and continued with Duncan test Î± 0,05 use SPSS program version 13.0. The results showed that treatment with seaweed meal significantly decreased to body weight, but had not affected to carcass percentage, thorax percentage and abdominal fat percentage, for the analysis materials on meat fat level and cholesterol apparently treatment using seaweed meal 7% can lower meat fat level, and cholesterol.Keyword: seaweed meal, broiler chickens, fat, cholesterol.